Merger Raksasa Digital dan Ancaman Persaingan Usaha: Studi Kasus Grab–GoTo di Indonesia - Moch Fajar Yusrivandana; Odi Boy Pramana Hutajulu; Rachmaliani Rofiqoh (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This article analyses the potential merger between two major technology companies in Southeast Asia, Grab and GoTo, with a focus on its implications for competition law in Indonesia. Using a normative juridical and comparative approach, the article evaluates possible violations of Law No. 5 of 1999 and considers the precedent of Grab's acquisition of Uber in 2018. It finds that such a merger poses a risk of creating significant market dominance, raising entry barriers for new competitors, and weakening the bargaining position of consumers and partners. However, the merger may also be viewed as a strategic response to the dominance of foreign digital platforms. Therefore, the active role of the Indonesian Competition Commission (KPPU) and adjustments in competition policy are urgently needed to address the challenges posed by cross-border digital consolidation